A History of Chilean Journalists Temporalities (1973-2013)? - Faure, Antoine (Revista de Historia Social y de las Mentalidades, 2018)
Based on debates about the matter of communication history, and its territories in Chilean case, we suggest implementing archaeology of journalism about its temporalities transformations. We bet that this approach helps to enrich the analysis of the relation between journalism and politics. To defend this argument, we justify the interest of developing a history of journalistic temporalities, and we report the objectives, hypothesis and methodology of an incipient research, about Chilean case (1973-2013).
Keywords: Journalism; Historiography; Archaeology; Temporalities; Polity